Age-Related Differences in Anterior Cruciate Ligament Remnant Vascular-Derived Cells. (June 2014) - Uefuji, Atsuo; Matsumoto, Tomoyuki; Matsushita, Takehiko; Ueha, Takeshi; Zhang, Shurong; Kurosaka, Masahiro; Kuroda, Ryosuke
Background: The anterior cruciate ligament (ACL) does not heal spontaneously after injury, and patients of different ages respond differently to treatment. CD34+ stem/progenitor cells derived from the ACL remnant and associated tissues contribute to tendon-bone healing, but the relationship between age and the ACL's healing potential has not been clarified. Hypothesis: The ACL remnant and associated tissues from adolescent patients have more CD34+ cells, and this population of cells from younger patients exhibits a higher potential for proliferation and differentiation in vitro. Study Design: Descriptive laboratory study. Methods: Ruptured ACL remnants and associated tissues were harvested from 28 patients (mean age, 24.6 ± 1.6 years) who had undergone primary arthroscopic ACL reconstruction. Patients were divided into 3 patient groups by age: 10-19 years (teens group; n = 10), 20-29 years (20s group; n = 10), and ≥30 years (30s group; n = 8). The ACL remnant cells were characterized using fluorescence-activated cell sorting (FACS). Expansion potential was evaluated using population doubling (PD), and multilineage differentiation potential was assessed and compared. Results: The FACS analysis showed numerous CD34+ cells in the teens group compared with the 30s group (mean, 25.4% ± 7.9% vs 16.9% ± 3.9%, respectively; P = .044). The PD results indicated that the teens group had a significantly higher expansion potential than the 30s group at passage 3 (mean, 3.3 ± 0.2 vs 2.8 ± 0.2, respectively; P = .039). Young ACL remnant cells had a higher potential for osteogenic differentiation according to alkaline phosphatase activity (teens group, 169.5 ± 37.9 × 10 ng/mL vs 30s group, 64.9 ± 14.6 × 10 ng/mL; P = .029) and osteocalcin gene expression (teens group, 1.0 ± 0.25 vs 30s group, 0.39 ± 0.01; P = .01). In addition, the teens group displayed a higher differentiation potential to angiogenic lineages (acetylated low-density lipoprotein/ Ulex europaeus lectin-stained cell counts) than other groups (teens group, 15.9 ± 1.9 vs 20s group, 8.9 ± 1.3 [ P = .04]; teens group, 15.9 ± 1.9 vs 30s group, 7.2 ± 1.5 [ P = .008]) and also tube length (teens group, 6939 ± 470 μm vs 30s group, 4119 ± 507 μm; P = .009). Conclusion: The ACL remnants of adolescent patients had more CD34+ cells, and those cells had a higher potential for proliferation and multilineage differentiation in vitro. Clinical Relevance: During remnant-preserving or remnant-transplanted ACL reconstruction, surgeons should consider the patient's age when predicting the healing potential.